Modelling Diesel Combustion - Lakshminarayanan, P. A.; Aghav, Yoghesh V.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
The diesel engine is the most efficient combustion engine today and it plays an important role in transport of goods and passengers by land and sea. However, the emissions must be controlled without sacrificing the legendary fuel economy of the diesel engines. These important drivers have caused innovations in diesel engineering like re-entrant combustion chambers in the piston, lower swirl support and high pressure injection, in turn reducing the ignition delay and hence the nitric oxides. This book is a detailed discussion of diesel combustion phenomena like ignition delay, fuel air mixing, rate of heat release, and emissions of smoke, particulate and nitric oxide. It enables quantitative evaluation of these important phenomena and parameters. Most importantly, it attempts to model them with constants that are independent of engine types. This work recognises the importance of the spray at the wall in precisely describing the heat release and emissions for most of the engines on and off road. It gives models for heat release and emissions. Every model is thoroughly validated by detailed experiments using a broad range of engines. Throughout the book, the models use constants that are independent of engine type or design and hence they could be applied by the designer and researcher for a general engine. All the models not only describe the trends of important parameters but also quantitatively close to the experimentally observed results. The enhanced understanding of the phenomena like turbulent flows, high-pressure sprays naturally converges to quantitative prediction using multi-dimensional CFD tools to reveal finer details of in-cylinder processes of diesel combustion. The CFD tools are introduced with case studies in two chapters of the book to help study innovative combustion concepts and improve engine designs in terms of emissions reduction and fuel economy.
Phenomenology of Diesel Combustion and Modelling -- Experiments -- Turbulent Structure of the Diesel Spray -- Ignition Delay in a Diesel Engine -- Heat Transfer -- Heat Release in Indirect Injection Engines -- Mixing Correlations for Smoke and Fuel Consumption of Direct Injection Engines -- Heat Release in Direct Injection Engines -- Hydrocarbons from DI Diesel Engines -- Hydrocarbon Emissions from Spark Ignition Engines -- Smoke from DI Diesel Engines -- Oxides of Nitrogen from Direct Injection Diesel Engines -- Particulate Matter from Direct Injection Diesel Engines -- Multi-dimensional Modelling of Diesel Combustion: Review -- Multi-dimensional Modelling of Diesel Combustion: Applications.
Keywords: Engineering; Hydraulic engineering; Engineering design; Pollution; Engineering; Automotive Engineering; Pollution, general; Engineering Design; Classical Continuum Physics; Fluid- and Aerodynamics; Engineering Fluid Dynamics